Biliometric analysis on nanomaterials applied to the fertilizer industry - Morgado, Mariana Rodrigues; Pires, Ricardo Francisco; Dantas, Sandra Cristina (Research, Society and Development, 2024)
With the constant population increase, pressure has been placed on agricultural systems with the aim of increasing production and making it more efficient. A promising solution to this would be the use of nanomaterials in the production of fertilizers, as nanotechnology encompasses a range of possibilities regarding the mechanisms and interactions of materials at the nanoscale. However, as it is a new technology and the particularities of its mechanisms are often still unknown, the studies currently found on nanotechnology cover more of its possibilities of use than its mechanisms of action. For fertilizers, there is a need to understand how the biochemical, molecular and physiological pathways that involve nanoparticles can increase the efficiency of plant development, and as a consequence, their productivity. Given the lack of bibliometric reviews addressing nanomaterials in fertilizers, this study aims to assess the historical evolution of this research field. To this end, a bibliometric study was carried out on publications on this topic published in the last 13 (thirteen) years available in the Web of Science and Scopus databases. From the bibliometric analysis, the expansion of nanotechnology in the agricultural field was identified, pointing to a potential for resolving obstacles faced by traditional fertilizers. However, there was a need for studies aimed at clarifying the relationships between fertilizers and plant physiology.